2010
DOI: 10.1007/s10554-010-9669-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of athletes’ heart by tissue Doppler and strain/strain rate imaging

Abstract: After regular and prolonged training, some physical and structural changes occur in the heart. Strain (S) imaging and Strain Rate (SR) imaging are new and effective techniques derived from tissue Doppler imaging (TDI) which examine systolic and diastolic functions. The aim of the present study was to evaluate left ventricular TDI and S/SR imaging properties in athletes and sedentary controls. The study population consisted of 26 highly trained athletes (group I) and age, sex and body mass index (BMI) adjusted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
1
15
2
1
Order By: Relevance
“…28 Another possible explanation for this phenomenon is the hypothesis that under resting condition, the untwisting of the left ventricle occurs at a lower velocity (as also demonstrated by an increased IVRT), with a consequently slower decay in LV pressure needed to generate the suction forces 40 ; however, the untwisting forces may become more relevant during exercise and at higher heart rates to generate more efficient filling of the left ventricle. 41 Our results are partially different from those of previous studies, which are largely heterogeneous: the E/A ratio was reported to be unchanged by some authors 42,43 but increased by others 16,37 ; certain studies reported increased E-wave velocity, 20,37 whereas most the others showed that it was unchanged 14,36,37 ; and e 0 velocity was increased in some studies 18,37,43 and unchanged in others. 14,16,36 These marked differences are likely due to the restricted and selected athlete populations included in previous studies, which do not allow a complete picture of diastolic function in athletes.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…28 Another possible explanation for this phenomenon is the hypothesis that under resting condition, the untwisting of the left ventricle occurs at a lower velocity (as also demonstrated by an increased IVRT), with a consequently slower decay in LV pressure needed to generate the suction forces 40 ; however, the untwisting forces may become more relevant during exercise and at higher heart rates to generate more efficient filling of the left ventricle. 41 Our results are partially different from those of previous studies, which are largely heterogeneous: the E/A ratio was reported to be unchanged by some authors 42,43 but increased by others 16,37 ; certain studies reported increased E-wave velocity, 20,37 whereas most the others showed that it was unchanged 14,36,37 ; and e 0 velocity was increased in some studies 18,37,43 and unchanged in others. 14,16,36 These marked differences are likely due to the restricted and selected athlete populations included in previous studies, which do not allow a complete picture of diastolic function in athletes.…”
Section: Discussioncontrasting
confidence: 68%
“…[14][15][16][17][18]36,37 However, within the broad spectrum of sport disciplines included in the present study, we observed a small but nonnegligible subset of athletes (3%) with E/A ratios > 3.0, sometimes up to 4.8. Therefore, a practical clinical consequence of this observation is that in elite athletes, LV filling should not raise suspicion of a restrictive filling pattern, despite the marked increase of E/A ratio (>3) and the presence of LA enlargement, 38,39 In this context, the normal DTI e 0 velocity and E/e 0 ratio, the normal PASP, and the overall clinical picture may help avoid the misdiagnosis of a pathologic cardiac condition.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…A few studies reporting segmental strain in the basal LV septal and lateral wall segment found deformation to be either concomitantly similar, 145 concomitantly higher in ATH than in CON, 134 or higher in CON in the basal septum but not in the basal lateral LV wall.…”
Section: 90 105 119 134 145 157mentioning
confidence: 99%